Policy planning and local government - Hambleton, Robin (London, United Kingdom : Hutchinson & Co., Ltd., 1978)
This book is intended to deepen understanding of these changes which may yet herald the development of a learning local government and a revitalization of local politics.
Part One. Moves towards learning -- Part Two. Area approaches in britain and america -- Part Three. Area management case studies -- Part Four. A learning Local government.
Includes index.
Keywords: GOVERNMENT -- LOCAL